Evaluation of thermal behavior of a wall construction system in the high andean zone using an experimental module - Molina Fuertes, Juan Omar (2024)
This article aims to evaluate the thermal behavior of a construction system consisting of fired red clay brick walls with cavities, commonly used in large cities in Peru and increasingly adopted in high-altitude Andean areas without being evaluated for frost climates. Consequently, an experimental module was constructed at a real scale at 4500 masl. The experimentation carried out over 49 days shows that the thermal delay and decrement factor are 4 hours and 0.27, respectively, with the daily hourly average thermal amplitude indoors being 6.4°C and outdoors being 17.1°C. Additionally, the numerical study using EnergyPlus software and the implementation of the equivalent model of a set of homogeneous layers for heterogeneous materials, which dynamically considers the heat transfer modes by conduction, convection, and radiation, achieve good agreements of the indoor temperature between the measured and simulated values with R2 indices of 0.87 and RMSE of 0.91, validating the experimental module model.